Immobilization of a copper complex based on the tripodal ligand (2‐aminoethyl)bis(2‐pyridylmethyl)amine (uns‐penp). Issue 5 (9th March 2021) - Brückmann, Tim; Becker, Jonathan; Turke, Kevin; Smarsly, Bernd; Weiß, Morten; Marschall, Roland; Schindler, Siegfried
Abstract: A new derivative of the ligand (2‐aminoethyl)bis(2‐pyridylmethyl)amine (uns‐penp), capable for covalent immobilization on silica, was synthesized. Silica powder for column chromatography and mesoporous monoliths served as surface material. Functionalized silica was sufficiently characterized with reflectance UV/Vis and FTIR techniques. Copper(I) was successfully complexed with the immobilized ligand and exhibits reversible reactivity towards dioxygen at low temperatures. Suspending the oxygen species with toluene at low temperatures led to selective oxygenation to benzaldehyde, determined by GC‐MS. Copper(I) complexes with the ligands Me‐PTS‐uns‐penp and Me‐Prop‐uns‐penp were prepared and characterized to model the reaction behavior towards dioxygen in solution. Additionally, solid copper peroxido complexes with these ligands were obtained by precipitation with the sterically demanding anion tetraphenylborate. Furthermore, these complexes could be obtained in a reversible reaction by treating corresponding copper(I) complexes with dioxygen. With all oxygenated copper complexes catalytic oxidation of toluene was observed. Abstract :